PERSPEKTIF ANALISIS FUNDAMENTAL DALAM MEMPREDIKSI BID-ASK SPREAD SAHAM - Wahyu Ramadhani; Tumirin Tumirin (LPPM STIE Muhammadiah Bandung, 2025)
The capital market plays an important role in supporting economic growth through the efficient allocation of financial resources. One of the key indicators in assessing market efficiency is the bid-ask spread, which reflects the level of liquidity and information asymmetry among market participants. The context of a company’s fundamental information, such as financial ratios, can serve as a signal that influences investor decisions and risk perceptions toward a stock. This study aims to analyze the effect of fundamental financial ratios consisting of Return on Assets (ROA), Debt to Equity Ratio (DER), and Tobin’s Q on the bid-ask spread in the capital market. The method used is a quantitative approach with multiple linear regression analysis on secondary data from manufacturing companies in the food and beverage subsector listed on the Indonesia Stock Exchange for the 2020–2024 period. The results indicate that DER does not have a significant effect on the bid-ask spread, while ROA and Tobin’s Q have a significant effect. Simultaneously, the three variables have a significant effect on the bid-ask spread. These findings indicate that fundamental financial ratios can provide important signals for investors in assessing risk and stock trading efficiency in the capital market.